The State in Classical Laissez-Faire, Its Crisis, and the Establishment of Fordism - Bonanno, Alessandro (The Legitimation Crisis of Neoliberalism, 2017)
This chapter stresses the point that contrary to arguments proposed by neoliberals, the state has consistently been a relevant actor in the organization of the economy and society. It indicates that the role played by the state was fundamental in the expansion and stability of capitalism in its early stages, during the laissez-faire era of the nineteenth century and under Fordism in the twentieth century. This argument is illustrated through a review of salient aspects of classical liberal theories of the state such as those of John Locke, Adam Smith, Jeremy Bentham, and John Stuart Mill and a brief review of the theory of Marx and early twentieth century contributions such as those of Karl Polanyic and John M. Keynes. An analysis of the theories of the role of the state under Fordism is proposed in the final sections of the chapter.
Sociology
Keywords: Fordism; MARX; Karl; 1818-1883; double movement; economic sociology; organizational studies; regulated capitalism

Treble Troubles? Marketization, Social Protection and Emancipation Considered Through the Lens of Slavery - Davidson, Julia O’Connell (The Commonalities of Global Crises, 2016)
This chapter considers white European and American thinking on transatlantic slavery historically and, more briefly, in relation to today’s antislavery movement. Combining historical longue durée and a critical engagement with Nancy Fraser’s neo-Polanyian position, O’Connell Davidson shows that abolitionists were, and are, hard to fix as proponents of either market freedom or social protection, or indeed of ‘emancipation’. The postabolition experience of freed slaves shows that marketization, social protection and emancipation are not fully disarticulable political forces, suggesting that the idea of the ‘triple movement’ may be less useful for those committed to a politics of nondomination than it may initially appear.
Sociology; Political Science
Keywords: economics; public choice; slavery; social choice; social inequality; social protection; social structure; triple movement; welfare economics

Local Embeddedness - Pickles, John (International Encyclopedia of Geography: People, the Earth, Environment and Technology, 2016)
In economic geography and economic sociology, embeddedness refers to the ways in which relational, institutional, and cultural contexts shape economic life. In contrast to the undersocialized and utilitarian assumptions of neoclassical economics, rational choice theory, and new institutional economics, theories of embeddedness focus on the ways in which markets and society are variously articulated in particular societies, organizations, and places. Embeddedness in this sense is associated first and foremost with the work of Karl Polanyi. Polanyi argued that the market generally sought to disembed itself from social regulation, while society responded by attempting to socialize and regulate (re-embed) the excesses of unregulated markets. It is also associated with the work of Granovetter in economic sociology, who cautioned against oversocializing, as well as undersocializing, the economy, in favor of a much more detailed analysis of the specific ways in which social relations structured economic practices.
Geography; Sociology
Keywords: POLANYI; Karl; 1886-1964; culture; economy; embeddedness; institutions; society; undersocialized

Penser la pluralité des monnaies à partir de Polanyi : un essai de typologie - Blanc, Jérôme (ERES, 2014)
A large number of currencies has emerged for thirty years, far beyond the national currencies alone. It includes systems created by groups of citizens, others by territorial communities, and others by private companies for their own benefit. These currencies take various forms, ranging from electronic money on smart cards to settlement systems ...
Sociology
Keywords: currencies; modern currencies

Marxism After Polanyi - Burawoy, Michael (Marxisms in the 21st Century: Crisis, Critique and Struggle, 2013)
KM - What should we do with Marxism ? For most the answer is simple. Bury it ! Mainstream social science has long since bid farewell to Marxism. The approach adopted here is that Marxism is a living tradition that enjoys renewal and reconstruction as the world it describes and seeks to transform undergoes change ... However, Marxsm cannot simply mirror the world. It seeks to change the world, but changing such a variegated world requires a variegated theory that keeps up with the times and accommodates places.
Sociology
Keywords: MARX; Karl; 1818-1883; Marxism; fictitious commodities

Understanding the “economization” of social formations - Jessop, Bob (The marketization of society: economizing the non-economic - Editors - Uwe Schimank, Ute Volkmann, 2012)
A critical review of nine dimensions of economization of social relations and their repercussions on societal dynamics. Discusses fictitious commodification, financialization, finance-dominated accumulation, and issues of ecological dominance. Bibliographic note: Book contains selected papers from conference on Marketization of Societies, organized at Bremen University, 1-2 June 2012. This is the pre-print version of a planned conference collection with a commercial publisher.
Sociology
Keywords: fictitious commodification; fictitious commodities; financialization

La société contre le marché - Skornicki, Arnault (The Life of Ideas, 2012)
A propos de : Karl Polanyi, La Subsistance de l'homme. La place de l'économie dans l'histoire et dans la société, Flammarion
History; Sociology
Keywords: capitalisme; commerce; marché

After Neoliberalism - Antonio, Robert J. (The Wiley-Blackwell Companion to Sociology, 2011)
This chapter contains sections titled: * Clashing Models of Capitalism: Hayek VS. Polanyi * Market Liberalism's Return: From the “Not Quite Golden Age” to the “Great U - Turn” * Hegemonic Neoliberalism: From Crest to Crisis to Emphatic Reassertion(?) * Capitalism at the Point of Inflection: Neoliberalism's Wake * Conclusion * References
Sociology
Keywords: 2008 financial meltdown; HAYEK; Friedrich A. von (Friedrich August); 1899-1992; Hayek's and Polanyi's classic texts; New Deal; The Great U-Turn; ascendant neoliberalism; cutting edge issues; great recession; hegemonic culture; neoliberalism; neoliberalism's wake; self-regulating market

Polanyi on Markets, Democracy and the Crisis of Liberalism - Ebner, Alexander (The Beginnings of Scholarly Economic Journalism, 2011)
Karl Polanyi, who was born in 1886 in Vienna and died in 1964 in Pickering, Ontario remains a most influential theoretical figure in the social sciences, in particular stimulating both analytical and policy-related concerns that are related with the new institutionalism in economics, sociology and political science. Polanyian insights on the political economy of economic development from an institutional perspective have persistently shaped a variety of discourses that range from the theory of the welfare state to research in comparative economic systems and economic anthropology. Polanyi’s “Great Transformation” may be singled out as a key contribution to both the domains of economic sociology and political economy, as it addresses basic tensions between the developmental dynamics of the market economy and the institutional substance of political democracy (Block 2001).
Sociology; Political Science
Keywords: crisis of liberalism; early writings; methodology; methodology of the social sciences

The ordering of change: Polanyi, Schumpeter and the nature of the market mechanism - Harvey, Mark; Metcalfe, Stan (Markets, Rules and Institutions of Exchange, 2010)
Sociology
Keywords: SCHUMPETER; Joseph Alois; 1883-1950; market mechanism

Markets Against Society: Labor's Predicament in the Second Great Transformation - Webster, Edward; Lambert, Robert (The ISA Handbook in Contemporary Sociology: Conflict, Competition, Cooperation, 2009)
Sociology
Keywords: labour movement; northern compromise; second great transformation

Where Does the Market Come From? Why the Controversy Between Polanyi's "Substantivists" and "Formalist" Neoclassical Protagonists of a Universal Market Was Never Solved" - Heinsohn, Gunnar (Property Economics: Property Rights, Creditor’s Money and the Foundations of the Economy, 2008)
In Property Economics: Property Rights, Creditor’s Money and the Foundations of the Economy - Metropolis-Verlag, 2008.
Sociology; Economics
Keywords: formalist; substantivist

The Politics of Liquid Modernity: Polanyi and Bauman on Commodification and Fluidity - Christodoulidis, Emilios (Liquid Society and Its Law, 2007)
Book edited by Jirí Pribán This collection of essays brings together Zygmunt Bauman and a number of internationally distinguished legal scholars who examine the influence of Bauman's recent works on social theory of law and socio-legal studies. Contributors focus on the concept of 'liquid society' and its adoption by legal scholars. The volume opens with Bauman's analysis of fears and policing in 'liquid society' and continues by examining the social and legal theoretical context and implications of Bauman's theory.
Sociology
Keywords: BAUMAN; Zygmunt; commodification; fluidity; law / jurisprudence; liquid modernity; philosophy; political philosophy

Globalization - McMichael, Phillip (The Handbook of Political Sociology states, civil societies, and globalization, 2005)
Philip McMichael casts a critical eye on the process of globalization suggesting that it takes different forms across time and space. He specifies contemporary globalization as a discursive project, geared to institutionalizing corporate markets through multilateral and regional economic agreements driven by powerful states. From this perspective of depicting globalization as an exercise in power, he examines political countermovements to globalization. Global justice movements, he argues, are globalization’s “historical and relational barometer,” and they operate at various, but often interrelated, scales. Work- ing from Karl Polanyi’s “double movement” of implementation of and resistance to economic liberalism, McMichael questions the adequacy of Polanyi’s formulation for the elaboration of market rule in the twenty-first century. This question concerns the conventional interpretation of “sovereignty” as the centerpiece of nation-state formation, including the development of citizenship. Here, globalization is viewed through the lens of a sovereignty crisis, where corporate market rule compromises the social contract upon which the state/citizen relation is founded. The crisis is expressed differently across the world, as the impact of market rule generates alternative social movement conceptions of sovereignty, especially in the global south where corporate globalization is realized through a drastic intensification of social exclusion.
Sociology
Keywords: counter-movement; critique; double movement; globalization; political sociology

The Great Depression and the Decline of Liberal Capitalism: Polanyi and Schumpeter - Trigilia, Carlo (Economic Sociology, 2002)
This chapter contains section titled: * Market Domination and Society's Self-Defense * The Decline of the Bourgeoisie and Anti-Capitalist Policies * Analytical Convergence and Political Divergence
Sociology
Keywords: SCHUMPETER; Joseph Alois; 1883-1950; capitalism; depression; economic level; economic sociology; international relations; social conditions

Chapter 6: Our time - Heiskala, Risto (Will Europe Work?, 2001)
The article focuses on Europe in the age of global networks and flowing identities. In the article the author discusses the articulation of Europe. He starts with a discussion on the identity of Europe, goes on with a discussion of globalization and closes with an attempt to tie these two themes together. He then raises, in a new context, sociologist Karl Polanyi's question: "What Kind of a Time Is Our Time?" Throughout the article, specific emphasis is put on the European Union, as this network state currently uniting fifteen and in the nearest future possibly twice as many European states as today is often what is referred to combined with the term "Europe", even if it would be a mistake to believe that these two are identical. The article also throws light on the affect of Islam on the countries of Europe. In several European countries there are enclaves of millions of Muslim migrant workers and there are Muslim countries at the borders of Europe in North Africa and the Middle East.
Sociology
Keywords: Europe; Islam; globalization; identity (philosophical concept); immigrants

Going public with Polanyi in the era of Trump * - Burawoy, Michael (The Routledge International Handbook of Public Sociology, 2021)
After considering different possible elements of the ‘Trump era,’ I will turn to The Great Transformation to periodize capitalism into three waves of marketization and their counter-movements. In the first wave, we follow the commodification of land, money and especially labor, so-called fictitious commodities, and the local counter-movements marketization inspired, reaching to the level of the state. In the second wave, the focus turns on the way marketization generated a reaction from states, seeking to regulate commodification – in other words, processes of de-commodification. Given the tension between capitalism and democracy, in Polanyi’s view essentially two forms of regulation were possible: either democracy suppresses capitalism and we get socialism, or capitalism suppresses democracy and we get fascism. He neither paid much attention to the popular forces that led in either direction nor to the possibility of a compromise between capitalism and democracy that reigned in three decades after World War Two. Beginning in the 1970s, we witnessed the beginning of a third wave of marketization – more commonly known as neoliberalism – that Polanyi did not anticipate. I attribute his failure to anticipate another wave of marketization to the contradictory pressures of accumulation that are temporarily alleviated by commodification. In this third wave, I show how democracy is discredited, and consensus politics dissolves into polarizing movements within and beyond parliamentary politics. The lived experience driving these movements, I argue, revolves around processes of re-commodification and ex-commodification of nature, money, labor and knowledge. This is the terrain upon which sociology must engage its publics. I highlight two approaches, both founded on an organic public sociology that engages directly with publics. On the one hand, there is the empathic public sociology that wades into communities in order to comprehend the distinctive ‘deep narrative’ of right wing populism, typified by Arlie Hochschild’s Strangers in Their Own Land. On the other hand, there is the affirmative public sociology that creates a collective vision based on a dialogue with the practitioners of real utopias, typified by Erik Wright’s How to Be an Anti-Capitalist in the Twenty-First Century.
Sociology
Keywords: Trumpism; marketization; public sociology

Karl Polanyi: The Great Transformation - Ebner, Alexander (Schlüsselwerke der Wirtschaftssoziologie, 2021)
Karl Polanyi war in jungen Jahren Zeitzeuge der vielschichtigen ökonomischen, sozialen und politischen Umwälzungen in der österreichisch-ungarischen Donaumonarchie. 1886 in Wien geboren, wuchs er in Budapest auf, wo er Rechtswissenschaft und Philosophie studierte, um dann nach der Zerschlagung der ungarischen Räterepublik nach Wien zurückzukehren. Dort schrieb er für die wirtschaftspolitische Wochenzeitschrift „Österreichischer Volkswirt“.
Keywords: biography

Ecology, Democracy, and COVID-19: Rereading and radicalizing Karl Polanyi - Ryan, J. Michael (COVID-19: Volume I: Global Pandemic, Societal Responses, Ideological Solutions, 2020)
The SARS-CoV-2 virus, and the associated COVID-19 pandemic, is perhaps the greatest threat to life, and lifestyles, the world has known in more than a century. The scholarship included here provides critical insights into the ethics and ideologies, inequalities, and changed social understandings that lie at the heart of this pandemic. This volume maps out the ways in which the pandemic has impacted (most often disproportionately) societies, the successes and failures of means used to combat the virus, and the considerations and future possibilities – both positive and negative – that lie ahead. While the pandemic has brought humanity together in some noteworthy ways, it has also laid bare many of the systemic inequalities that lie at the foundation of our global society. This volume is a significant step toward better understanding these impacts. The work presented here represents a remarkable diversity and quality of impassioned scholarship and is a timely and critical advance in knowledge related to the pandemic. This volume and its companion, COVID-19: Volume II: Social Consequences and Cultural Adaptations, are the result of the collaboration of more than 50 of the leading social scientists from across five continents. The breadth and depth of the scholarship is matched only by the intellectual and global scope of the contributors themselves. The insights presented here have much to offer not just to an understanding of the ongoing world of COVID-19, but also to helping us (re-) build, and better shape, the world beyond.
Keywords: COVID-19; disease & health Issues; health

This freedom kills: Karl Polanyi’s quest for an alternative to the liberal vision of freedom - Brie, Michael (Karl Polanyi and twenty-first-century capitalism, 2020)
The chapter reconstructs the emergence and formulation of Karl Polanyi's central research question: How is responsible freedom possible in a complex modern society? The origins of this question in the time before the First World War and the confrontations with the challenge of neoliberalism and fascism are discussed. It is shown that Karl Polanyi's concept of freedom has four dimensions. Polanyi connects negative, positive, substantial and social freedom with each other and formulates a highly innovative research programme which forms the basis for The Great Transformation and later works.
Sociology; Economics
Keywords: freedom; freedom in a complex society

Commodified money and crustacean nations - Desai, Radhika (Karl Polanyi and twenty-first-century capitalism, 2020)
Though Polanyi referred to three distinct fictitious commodities, one, money, and the fate of the apex structure that commodified it, the gold standard, structured The Great Transformation’s narrative. Despite this centrality of money and its commodification to Polanyi’s masterwork, there is near-deafening silence in Polanyi scholarship on money as a fictitious commodity. This chapter ends it. It traces Polanyi’s understanding of fictitious commodities to its sources in classical political economy and explains how the near total dominance of the antithetical tradition of neoclassical economics obscures understanding. The chapter also argues that the resulting argument shared a great deal with the classical Marxist theories of imperialism and of uneven and combined development of previous decades, particularly their arguments about the centrality of powerful nation states to capitalism. It stresses another hitherto neglected aspect of Polanyi’s argument, that the double movement led to the emergence of ‘crustacean nations’. As such, the chapter argues, The Great Transformation contributes a great deal towards a new approach to understanding world affairs, geopolitical economy, which challenges Ricardian ‘universalist’ understandings and takes the ‘materiality of nations’ seriously. It, and Polanyi, are more relevant than ever in our ‘deglobalizing’ age of multi-polarity.
Sociology
Keywords: Marxism; fictitious commodities; imperialism; money

Introduction: Karl Polanyi in the twenty-first century - Desai, Radhika (Karl Polanyi and twenty-first-century capitalism, 2020)
This introduction places the contributions that follow in the context of Polanyi’s rising influence, its causes and effects, and of the key twenty-first century developments that make his oeuvre more relevant than ever. It emphasizes how the contributions push the boundaries of received understandings of Polanyi. While some contributions fill gaping holes, such as those on money as a fictitious commodity, others overturn received understandings, whether that of the double movement or fictitious commodities, or the provenance (Central European or American) of his principal ideas and concerns or how he understood socialism. Yet others demonstrate how amenable Polanyi’s ideas are to further development. Last but not least, the introduction outlines Polanyi’s historical diagnosis as it emerges from these innovative contributions and argues that the stark choice he felt faced European societies, socialism or fascism, is once again before us as we face the groundswell of nationalist and far right forces.
Sociology
Keywords: capitalism; contemporary relevance; fascism; socialism

The reality of society - Rotstein, Abraham (Karl Polanyi and twenty-first-century capitalism, 2020)
In these remarkably stirring reflections, delivered at the 2014 conference from which most of the contributions to this volume emerge, the late Abe Rotstein, Polanyi’s student and collaborator, recalls the projected sequel to The Great Transformation, to be titled Freedom and Technology. Whereas the former was built on a social sciences approach using institutional analysis, the sequel was to follow the intention Hegel expressed in the words ‘Wir die religiöse Vorstellung in Gedanken fassen’ (We want to turn religious expression into philosophical thought). Polanyi took religion seriously – not its outer ceremonial trappings but the important truths that lay behind and beneath these beliefs and practices. The sequel was to trace humanity’s progression through three major revelations: the knowledge of death, the discovery of our inner life and conscience, and the realization of freedom amid our social obligations. This was the idea of ‘the reality of society’ around which the whole book was to be built. It was the precursor of our cherished civil freedoms and closely connected with Polanyi’s idea of freedom in a complex society; it is also deeply threatened in an age of state and corporate cyber surveillance.
Sociology
Keywords: freedom; reality of society; technology

Fictitious ideas, social facts and the double movement: Polanyi’s framework in the age of neoliberalism - Thomasberger, Claus (Karl Polanyi and twenty-first-century capitalism, 2020)
In the last decades, Karl Polanyi has gained recognition as one of the most important social scientists of the twentieth century. His seminal book, The Great Transformation, is listed among twentieth- century classics. How can this book, written more than seventy-five years ago, be applied to the current conditions? In order to answer this question the chapter not only compares the civilization of the nineteenth century in Europe with our own epoch. It also reconstructs some of Polanyi’s most important insights, such as his critique of the liberal utopia (in its classical and neoliberal version), his interpretation of the double movement, his vision of the meaning of the industrial revolution, his understanding of the problem of freedom in a complex society and his idea of a necessary ‘reform of human consciousness’. The chapter closes with a discussion of the question of how Polanyi’s categories can be used fruitfully so as to throw light to the post-war era and our society today.
Sociology
Keywords: Great Transformation; The (Book); double movement; freedom in a complex society; liberal utopia; social facts

Ecology, democracy, and COVID-19: Rereading and radicalizing Karl Polanyi - Duzgun, Eren (Ecology, democracy, and COVID-19, 2020)
This chapter argues that Karl Polanyi’s economic sociology offers foundational concepts for a radical analysis of the social and ecological conditions that have caused the coronavirus pandemic. Furthermore, it shows that Polanyi’s work, often claimed for social democracy, has the potential to provide much more radical insights into the question as to how to “re-embed” our economies, thereby leading to a fundamental rethinking about the ways in which the present crisis can be overcome.
Sociology
Keywords: COVID-19